Hydrochemical Characteristics and Evaluation of Groundwater Quality of Tumkur Amanikere Lake Watershed, Karnataka, India - D. S. Rajendra Prasad; C. Sadashivaiah; G. Rangnna (E-Journal of Chemistry)
The study area, Tumkur amanikere lake watershed, is located 0.5 km away from Tumkur Town on National Highway No.4. The main source of water for this lake is Kallur village tank catchment area. The average rainfall in the area is 965 mm. The submersion area of the lake at MWL is 204 hectares. Groundwater samples were collected from 22 stations covering the area during the year 2008 and were analyzed for physicochemical characters. The type of water that predominated in the study area is Ca-Mg-Cl type, was assessed based on hydrochemical facies. Besides, suitability of groundwater for irrigation was evaluated based on sodium adsorption ratio, percent sodium, and the US salinity diagrams.